Effects of Different Nitrogen Forms and Competitive Treatments on the Growth and Antioxidant System of Wedelia trilobata and Wedelia chinensis Under High Nitrogen Concentrations - Huang, Ping; Shen, Fangyuan; Abbas, Adeel; Wang, Hao; Du, Yizhou; Du, Daolin; Hussain, Sadam; Javed, Talha; Alamri, Saud (Frontiers in Plant Science, 2022)
Nitrogen (N) is one of the essential nutrients for plant growth. Appropriate application of N can improve the N use efficiency (NUE) and significantly promote plants’ growth. However, under N toxic conditions, the relationship between the growth and antioxidant system of invasive plants under different N forms and competitive treatments is not fully understood. Therefore, in this study, the performance of invasive species Wedelia trilobata and its native species Wedelia chinensis was evaluated under two sets of N forms and ratios, namely, NH4+-N(AN)/NO3–-N(NN) = 2:1 and NH4+-N(AN)/NO3–-N(NN) = 1:2 along with two intraspecific and interspecific competitions under without N and high N level of 15 g N⋅m–2 year–1, respectively. Data regarding the growth indices, antioxidant enzyme activities, including peroxidase (POD) and catalase (CAT), malondialdehyde (MDA), and proline contents were determined. Results showed that for competitive treatments, growth status was better for interspecific competition than intraspecific competition. The plant biomass of W. trilobata was significantly higher than that of W. chinensis. N significantly promoted the plants’ growth in terms of leaf area and biomass yield, and the antioxidant enzyme activities were significantly increased under a high N treatment than that of the control. Among N forms/ratios, ammonium N (AN)/nitrate N (NN) = 2:1 significantly enhanced the enzyme activity, particularly in W. trilobata. Furthermore, for intraspecific competition, MDA contents of W. trilobata were significantly decreased compared to that of W. chinensis. In conclusion, our results showed that W. trilobata adapted well under competitive conditions through better growth and antioxidant defense system.